PENGARUH MINYAK MENTAH UBP LIRIK TERHADAP PERTUMBUHAN DEFOLIASI DAN BIOMASSA ANAKAN MANGROVE Bruguiera sexangula DI KELURAHAN PANGKALAN SESAI KOTA DUMAI - Taufik Herman; Bintal Amin; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in October 2012-January 2013 to study thegrowth, defoliation and biomass of mangrove seedling of Bruguiera sexangula whichwas contaminated by crude oil in Pangkalan Sesai Village of Dumai in Riau Province.The research used experimental method by direct observation on the field. The resultsshowed that treatment with different concentrations of crude oil, gave a significantimpact to the growth, leaf number, height, defoliation and leaf biomass of mangroveseedlings. Increasing diameter, stem biomass and root biomass of Bruguiera sexangulawas, however, not impacted by crude oil. Higher crude oil concentration added to theseedling lowered the growth and gave higher defoliation in mangrove Bruguierasexangula seedling.Keywords : Dumai, Crude Oil, Biomass, Defoliation, Growth, Bruguiera sexangula